For what value of x is log(x^2-x-6)-x=log(x+2)-4

For what value of x is log(x^2-x-6)-x=log(x+2)-4

For what value of x is log(x^2-x-6)-x=log(x+2)-4

For what value of x is log(x^2-x-6)-x=log(x+2)-4
The equation `log(x^2-x-6)-x=log(x+2)-4` has to be solved for x.`log(x^2-x-6)-x=log(x+2)-4`=> `log((x – 3)(x + 2)) – x = log(x + 2) – 4` => `log(x – 3) + log(x + 2) – x = log(x + 2) – 4` => `log(x – 3) = x – 4` log denotes logarithm to the base 10=> `x – 3 = 10^(x – 4)` => `x – 3 = 10^x/10000` Taking x = 4=> 4 – 3 = 1 and 10^4/10^4 = 1The solution of the equation is x = 4